EKSPLORASI PROSPEK USAHA MIKRO RUMAHAN PANGANAN EMPING MELINJO DI KABUPATEN BENGKULU UTARA (Studi Kasus di Desa Selubuk Kecamatan Air Napal) - Fitri Apriani; Endah Heryanti; Dewi Aprida (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2019)
The results showed based on the results of calculations using the data processed. The amount of profit empingmelinjo business is Rp. 1.750.154.- that the advantages of small industries empingmelinjo in Selubuk Village, Air Napal Sub-district, North Bengkulu Regency.Based on the results of research and analysis that have been done, it can be concluded as follows: A total of 13 respondents or 100% empingmelinjoentrepreneurs benefit from the business empingmelinjo in the effort.The highest profit that can be empingmelinjo entrepreneurs in the Village SelubukKecamatan Air Napal North Bengkulu regency of Rp. 2.317.000.- while the lowest Rp. 1,080,000.- The average revenue earned amounted to Rp 2,733,846 per month so that the average profit earned by emping businessmen is Rp 1.620.384,6 per month. The profitability of empingmelinjo industry in Selubuk Village is 2.45%, which means the business of empingmelinjo industry is profitable. The average total cost of empingmelinjo households in Selubuk Village is Rp 1,113,462 per month. The average profit of empingmelinjo producing business is Rp.1.750.154.-